Maximum Accuracy in MANET-Node-Localization Using Multi-Stage Trackerwith Less Time-Complexity - selvan.M, Arul; SelvaKumar.S, Dr (International Journal of Engineering and Technology, 2018)
An ad hoc network (referred as MANET), is also called as mobile ad-hoc network and also wireless ad hoc network, is automatic self-configuring, infrastructure-less wireless network of mobile devices, and itÂ widely used in various areas. Wireless sensor network composed of wireless sensor nodes and these nodes can do processing, sensing, computation and wireless communication. Because of its more functionality and low cost of energy consumption the wireless sensors are used widely in various areas such as ranging from sensors for environment, road safety,Â home, peer-to-peer messaging, vehicular ad hoc communications, health, disaster recovery operations, robots, weapons, defense, etc. The localization information is very important for the operation of MANET because of security, routing, and other needs. This articles mainly contracts with the network node station identification in wireless environment with maximum accuracy. There are many methods of localization exist for MANET, and this paper discusses, compares and explains the betterments through experimental localization methods. Localization process is a vital and essential part in lots of applications that signifies a supplementary procedure in a network function or sometime it can be a primary goal of the application. Localization, as an essential procedure is also desirable based on data mining and data fusion, efficient routing with the view of hierarchical data aggregation. The hierarchical aggregation method itself signifies beneficial function of all data networks as it decreases important energy consumption and saves bandwidth in ad hoc network. And also it makes sure of repeatability-of-tests through multiple test-environments which is a problematic task in many situations in wireless networks. Eventually the accuracy of the location identification is critical aspect of any algorithm and technique that will be the important aspect of this paper.Â Â